Impact of additive direct and maternal heritability on production efficiency traits in Jersey crossbred cattle - RATWAN, POONAM; KUMAR, MANOJ; KUMAR, ANSHUMAN; CHAKRAVARTY, A K; MANDAL, AJOY (The Indian Journal of Animal Sciences, 2018)
Variance components, direct and maternal heritability were estimated for milk production efficiency traits namely, milk yield per day of lactation length (MY/LL) and milk yield per day of calving interval (MY/CI) in Jersey crossbreds maintained at Eastern Regional Station of ICAR-National Dairy Research Institute, West Bengal (India). Data analyses were done using restricted maximum likelihood (REML) method with six alternative animal models (direct and including or excluding maternal associated effects). The best model was chosen after testing the improvement of the log-likelihood values and it revealed direct heritability estimates as 0.47 and 0.25 for MY/LL and MY/CI traits, respectively. Maternal heritability (0.14) was found to be important for MY/LL trait and permanent environmental maternal effect contributed 12% to the total phenotypic variance of the MY/CI. Direct heritability estimates were high (0.47) for MY/LL and moderate for MY/CI (0.25) trait suggesting that there is ample scope of improvement through selection for milk production efficiency traits in Jersey crossbred maintained at organized herds.